2015
DOI: 10.1007/s11230-015-9588-6
|View full text |Cite
|
Sign up to set email alerts
|

Meteterakis saotomensis n. sp. (Nematoda: Heterakidae) from Schistometopum thomense (Bocage) (Gymnophiona: Dermophiidae) on São Tomé Island

Abstract: Meteterakis saotomensis n. sp. is described from Schistometopum thomense (Bocage), a gymnophionan endemic to the oceanic island of São Tomé in the Gulf of Guinea. The specimens were assigned to Meteterakis Karve, 1930, based on the possession of a head with three rounded lips, not set-off from the body, the absence of interlabia and cordons, females with a long vagina and males with a preanal sucker, surrounded by a cuticularised rim and caudal alae that are supported by fleshy papillae. The new species is cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In addition to the spicule length, the new species is distinguishable from the eight congeners by the following characteristics of spicules: proximal end wide, funnel-shaped and ventrally bent vs. proximal end slightly widened in M. ishikawanae (Hasegawa 1987) and M. wonosoboensis Purwaningshi, 2015 or vs. proximal end straight in M. guptai Gupta &Naiyer, 1993 andM. triaculeata (Kreis, 1933) (Inglis 1958); surface smooth, vs. rough surface in M. saotomensis Junker et al, 2015; and spicule alae narrow vs. wider in M. baylisi Inglis, 1958, M. crombiei Bursey et al, 2005and M. sinharajensis Crusz & Ching, 1975.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations
“…In addition to the spicule length, the new species is distinguishable from the eight congeners by the following characteristics of spicules: proximal end wide, funnel-shaped and ventrally bent vs. proximal end slightly widened in M. ishikawanae (Hasegawa 1987) and M. wonosoboensis Purwaningshi, 2015 or vs. proximal end straight in M. guptai Gupta &Naiyer, 1993 andM. triaculeata (Kreis, 1933) (Inglis 1958); surface smooth, vs. rough surface in M. saotomensis Junker et al, 2015; and spicule alae narrow vs. wider in M. baylisi Inglis, 1958, M. crombiei Bursey et al, 2005and M. sinharajensis Crusz & Ching, 1975.…”
Section: Methodsmentioning
confidence: 92%
“…The spicule length, which has been regarded as a useful taxonomic character of the genus Meteterakis (e.g. Junker et al 2015), exhibits certain intraspecific variations. Moreover, the characteristic of spicule length sometimes overlaps with those of other congeners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ecology and behavior of all the island species are incompletely understood, including basic aspects of reproductive biology (e.g., L. palmatus) and dependence on particular habitats (e.g., P. newtoni, H. thomensis), which are likely important considerations for effective conservation management. Like most vertebrates, São Tomé and Príncipe's amphibians also serve as hosts for many parasites, including the fungal pathogen Bd and a recently described nematode (Meteterakis saotomensis; Junker et al 2015), but the diversity of this microfauna and potential impacts on the amphibian hosts are poorly known. For instance, a recent study identified cryptic infection of P. leveleve (misidentified as P. dispar in the study) tadpoles by Perkinsea protists (Chambouvet et al 2015) that have caused mass mortality events in the United States (Davis et al 2007).…”
Section: Future Researchmentioning
confidence: 99%